The effect of internet usage among employees during working hours towards their performance / Norhaiza Aziz - Aziz, Norhaiza (2013)
The popularity of social networking sites is relatively recent and the effect of online social networking (OSN) on employee productivity has not received much scholarly attention. The reason most likely lies in the social nature of social networking sites and OSN, which is assumed to have a negative effect on employee productivity and not bear organizational benefit. This research investigated recent Internet developments as seen in the social Web and specifically investigated the effect of OSN on employee productivity and what some of the consequences would be if employees were allowed unrestricted access to these networks. The findings concerning the nature of employees' OSN activities, employees' attitude or perceptions with regard to OSN in the workplace and how OSN can contribute or affect the productivity of employees (Ferreira, 2009). This research is to identify the effect of internet usage among IKBN Wakaf Tapai employees during working hours towards their performance. Therefore, this research study was held to make sure that the level performance among the employee did not decrease although they were using internet in workplace. The questionnaire and data was collected from 45 respondents of IKBN Wakaf Tapai, Terengganu. The data was analyzed by using Statistical Package for Social Science Software (SPSS) version 20.0.